Evaluation of pattern of dyslipidemia in acute stroke in type 2 diabetics (Journal of Dhaka National Medical College & Hospital, 2017)
Background: Stroke is a neurological disease, which is a major cause of death and disability worldwide and third leading cause of death in Bangladesh. Diabetes mellitus is more commonly accompanied by dyslipidemia which is the leading cause of atherosclerotic changes in blood vessels and which also increases the risk of stroke.Aims: To observe the pattern of dyslipidemia in acute stroke in type 2 diabetics.Methodology: It was a hospital based cross sectional observational study in DMCH, Dhaka. Total 100 patients of acute stroke with type 2 diabetes were enrolled in this study by purposive sampling after written informed consent. The initial clinical diagnosis of stroke was done from history obtained from patient himself or his/her attendant and confirmed by CT/MRI of brain. Patients taking lipid lowering drugs, brain tumour, meningitis, viral encephalitis and/or metabolic encephalitis, hypothyroidism and nephrotic syndrome were excluded. A standard preformed questionnaire was designed and filled up for each patient. Collected data were checked, verified for consistency and edited for finalized result. Data cleaning, validation and analysis was performed using the SPSS/PC and graph and chart by MS excel.Results: Total 100 numbers of patients of acute stroke with type 2 diabetes patients admitted in DMCH were enrolled in this study. Eighty two (82.0%) patients had dyslipidemia and among them almost two third (60.0%) patients had total cholesterol ≤200 mg/dl, 64.0% had LDL >100 mg/dl, 81.0% had HDL less than target value and 58.0% had TG >150 mg/dl. Ischemic stroke and hemorrhagic stroke were found in 86(86.0%) and 14 (14.0%) respectively. Total cholesterol, LDL, HDL, TG were not significantly (p>0.05) different between two types of stroke.Conclusion: This study was undertaken to observe the patterns of dyslipidemia in acute stroke in type 2 diabetics. Lipid profiles almost alike between Ischemic stroke and Hemorrhagic stroke. Ischemic strokes were more common in this study. Diagnosis and proper management of dyslipidemia can be an important part of prevention of stroke.J. Dhaka National Med. Coll. Hos. 2017; 23 (01): 51-53